2016
DOI: 10.1177/0271678x15621575
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin rescues vascular, metabolic and learning deficits in apolipoprotein E4 transgenic mice with pre-symptomatic Alzheimer’s disease

Abstract: Apolipoprotein E ɛ4 allele is a common susceptibility gene for late-onset Alzheimer's disease. Brain vascular and metabolic deficits can occur in cognitively normal apolipoprotein E ɛ4 carriers decades before the onset of Alzheimer's disease. The goal of this study was to determine whether early intervention using rapamycin could restore neurovascular and neurometabolic functions, and thus impede pathological progression of Alzheimer's disease-like symptoms in pre-symptomatic Apolipoprotein E ɛ4 transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
112
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 49 publications
9
112
0
Order By: Relevance
“…The preservation of hippocampal and frontal CBF were associated with improved cognition in the old CR mice. This is also consistent with our previous findings that restoration of CBF in young mice modeling human AD could potentially prevent their cognitive decline in aging [30, 35]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The preservation of hippocampal and frontal CBF were associated with improved cognition in the old CR mice. This is also consistent with our previous findings that restoration of CBF in young mice modeling human AD could potentially prevent their cognitive decline in aging [30, 35]. …”
Section: Discussionsupporting
confidence: 93%
“…In addition to modulating eNOS, we previously demonstrated that mTOR inhibition reduces proinflammatory cytokine that breaks down BBB, and thus restores BBB integrity and CBF in mice that carries human APOE4 gene [35]. Furthermore, mTOR is able to clean up misfolded proteins (such as Aβ and cerebral amyloid angiopathy) via regulation of autophagy [36], therefore, it can further reduce athero-sclerosis and preserve neurovascular integrity, e.g., vascular density [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early interventions that can restore neurovascular deficits to normal could be critical in potentially preventing the development of AD-related neuropathology and cognitive impairment. In a recent study, using magnetic resonance imaging (MRI), Lin et al reported that young, asymptomatic APOE4 targeted-replacement mice treated with rapamycin had restored CBF and BBB integrity to the level of wild-type controls [2]. The preserved vasculature was associated with amelioration of incipient learning deficits of the APOE4 transgenic mice.…”
mentioning
confidence: 99%
“…Lin et al demonstrated that mTOR inhibition reduced proinflammatory pathways in brain vasculature that otherwise impair BBB integrity in the APOE4 transgenic mice [2]. Loss of BBB integrity is considered one of the initiating events that lead to AD-like pathological cascade in the APOE4 carriers [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation